Preparation and Voltammetric Application of a Zr(IV) Functionalized Spongolite for the Electrocatalytic Oxidation of Hydrazine - Carmo, Devaney Ribeiro do [UNESP]; Souza, Tamires Rocha [UNESP]; Maraldi, Vitor Alexandre [UNESP]; Serantoni da Silveira, Tayla Fernanda [UNESP] (Springer, 2018)
This study demonstrates an additional exploration of the possibilities of modifying the surface of spongolite spicules, a biogenic silica, in order to prepare natural inorganic composites for application in catalytic oxidation processes. In this context, a novel hybrid material was synthesized from the inorganofunctionalization of a spongolite with zirconium(IV) (EZr). This material was then reacted with potassium hexacyanoferrate(III) and applied in a subsequent reaction with copper ions. The obtained material (EZrCuH) was characterized by scanning electron microscopy (SEM), infrared spectroscopy (FT-IR), and cyclic voltammetry (CV). The CV of the graphite paste modified with EZrCuH exhibited two redox couples with midpoint potentials (E-theta,E-) equal to 0.36 and 0.74 V, attributed to the Cu-I/Cu-II and Fe-II(CN)(6)/Fe-III(CN)(6) processes (1.0 mol L-1, KCl pH 7.0, v = 20 mV s(-1)), respectively. The EZrCuH-modified graphite paste electrode presented electrocatalytic activity in the oxidation of different hydrazine concentrations and an analytical curve with a linear response of 8.0 x 10(-7) to 4.0 x 10(-5) mol L-1 (R-2 = 0.999, relative standard deviation = +/- 2% (n = 3)), and limit of detection of 8.33 x 10(-7) mol L-1 and an amperometric sensitivity of 8.21 mA mol(-1) L-1. Therefore, this material can be considered as a potential candidate for the manufacturing of electrochemical sensors intended for the easy and rapid detection of hydrazine substances.
Keywords: Spongolite; Zirconium(IV); Graphite paste electrode; Hydrazine